Epidemiological screening of pathogenicity factors associated with multidrug-resistant bacteria isolated in uroculture of hospitalized neonates in the lakes region from Rio de Janeiro. - Aleixo Albuquerque, Nayle; da Silva Pessoa, Nicolly; Delmaschio, Cathia; Lima Gondim, Priscila de Oliveira; Porto Santana, Felipe; de Athayde Campos, Daniel; Espindola Viana, Ruan; Gomes de Oliveira, Marcus Vinícius; Carvalho Rapagnã, Luciano; Viana da Silva, Gilson; de Souza , Cassius (Brazilian Journal of Implantology and Health Sciences, 2023)
The discovery of antimicrobials revolutionized the treatment of infectious diseases caused by bacteria, as they are drugs that contribute to reducing morbidity and mortality rates associated with infectious diseases (JANEBRO, et al., 2008). However, the irrational use of antimicrobial drugs represents one of the main concerns worldwide, since the misuse of these drugs accelerates the natural process of bacteria resistance to antibiotics (ZIMERMAN, 2010). In view of all these problems, the objective of this study was to evaluate the profile of resistance of bacteria identified in the urine culture of neonates who are hospitalized, based on the records of the Laboratory of Clinical Analysis of a hospital in the lakes region from Rio de Janeiro. To do so, we used the following methodologies: (i) literature review for contextualization of the problem and basis for discussion; (ii) and monitoring of a descriptive observational study that had as instrument the reports of records containing results of urine culture and antibiogram of neonatal patients, referring to the period from January 2020 to September 2021. The results showed a higher incidence of Escherichia coli (44% - 2020; 56% - 2021) among the microorganisms isolated in the analyzed urine cultures, followed by Klebsiella pneumoniae (14% - 2020; 28% - 2021). Antimicrobials from the β-lactam group caused high bacterial resistance, among the strains of different microorganisms analyzed, increasingly indicating the need for the replacement of these drugs in the clinic, in order to choose a better therapy for the patient. As in any infectious pathology, to establish appropriate prevention and treatment of community-acquired urinary tract infections, effective and continuous research is needed, with the goal of defining in detail the etiology and profile of bacterial resistance in regional, national, and international standards. It is hoped that these new data profiling the level of resistance in which microorganisms isolated from neonatal patients admitted under hospital regimen are found will be of great value to the academic community and to health professionals, providing users with increasingly accurate and quality treatment.